Team statistical determinants of victory in Brazilian basketball - Oliveira de Carvalho, E. M.; Leicht, A. S.; Nakamura, F. Y.; Okuno, N. M.; Alves Okazaki, V. H. (MOJ Sports Medicine, 2017)
Aim: The present study aimed to identify the team variables that better determine victory in Brazilian basketball in a variety of game dynamics (close, even and disparate games).